Revolutionizing Home Living Using Cyberspace Technology (International Journal of Food and Nutritional Sciences, 2022)
A computerized home integrates technology to automate and oversee various aspectsof the household, offering convenience, enhanced energy efficiency, security, and comfort. This setupincludes smart devices, sensors, and systems that allow for remote control and scheduling. The systemencompasses a variety of components, such as thermostats, lighting controls, security systems, andvoice assistants, all of which collaborate to streamline tasks, reduce energy consumption, and bolstersecurity. The process of home computerization results in the creation of intelligent living spaces thatcater to a connected lifestyle. The proposed system is designed to computerize homes with anaffordable and wireless infrastructure. Its primary focus lies in the development of an Internet ofThings (IoT)-based home automation system, facilitating remote control of various components viathe internet or automatic programming based on environmental conditions. By leveraging theNodeMCU IoT platform, a firmware is engineered to minimize the need for human intervention,ensuring the efficient operation of electrical devices. Different transmission modes enable seamlesscommunication between the user, NodeMCU, and household appliances. The primary control systemutilizes wireless technology, enabling remote access through smartphones via cloud server-basedcommunication. A data transmission network enhances the automation capabilities of the system. Withits user-friendly interface and straightforward installation process, this system effectively manageselectrical appliances within a household. The proposed system empowers users to exercise internetbasedcontrol over any load through the use of an ESP32 Wi-Fi module, resulting in increasedindependence, safety, convenience, control, comfort, and energy savings.